PARTISIPASI ANGGOTA PADA KELOMPOK TANI KALELONDI DESA KAUNERAN, KECAMATAN SONDER, KABUPATEN MINAHASA - Richo Richardo Turangan; Theodora M. Katindagho; Benu Olfie L.S (Sam Ratulangi University, 2017)
This study aims to determine the Members Participation in the Village Farmer Group Kalelon Kauneran District of Sonder Minahasa. The study lasted three months, the month of July 2016 until September 2016, ranging from preparation to preparation of research reports. The data used in this study are primary data and secondary data. The primary data obtained through interviews to respondents by using questionnaire and secondary data obtained through the office of the Village Kauneran. Data collection technique used census techniques are all members of the Farmers Group Kalelon of 20 people interviewed using a questionnaire. Analysis of the data in this study using the descriptive analysis and also using a Likert scale, with level 1 (underactive), 2 (active), 3 (highly active). The results showed, based on the Likert Scale, that the number of index Member Participation in Farmers Kalelon in the planning stage which also includes, liveliness and activeness followed meetings to provide input. Parisipasi members in the implementation phase also includes the activity, the activity of paddy rice cultivation, active in horticultural crop cultivation, active in post-harvest harvest to rice paddy, active in post-harvest harvest to horticultural crops, liveliness mengiktuti counseling, active in giving mandatory dues. Participation of members in the evaluation phase which include involvement in monitoring the group's activities, involvement in a variety of outcome measures farming activities. Participation of members of Kalelon farmer groups in the planning phase, the implementation phase and the evaluation phase were at 86, 5 is relatively high. Further analysis showed that the level of participation of members of the Farmer Group Kalelon on the score of 519 out of the range of the number of ideal scoring the highest score was 600 and the lowest score is 200. Suggestions in this research for members of farmer groups to improve their Kalelon activeness in following the extension because it are the main participants and entrepreneurs in the development of food security and the government should pay attention to what the needs of the farmer groups Kalelon for the development of farmer groups in general.Keywords: Participation, Member, Farmers Group Kalelon, Kauneran Village, Sonder District, Minahasa